Pengembangan Alat Pengenalan Bentuk Bangun Geometri Untuk Anak Usia Dini Berbasis Mikrokontroler - Mochamad Fajar Wicaksono; Muammar Qhadafhi (CCIT Journal, 2019)
The purpose of this study is to design geometry learning media for early childhood. The tool designed is an interactive introduction tool, so it is hoped can attract early childhood children to learn to recognize and remember geometric patterns. The main brain of the system created is Arduino Mega with microcontroller ATMega2560. The tool created has two modes, namely learning mode and question mode. In learning mode, early childhood can insert geometry objects into the tool, then the tool will provide a description of the image on the LCD and the sound associated with the object entered. In question mode, early childhood will be challenged to enter the geometry objects into the tool according to the question, then the tool will determine whether the geometry entered is correct or false. This learning media is expected to help early childhood to be able to recognize and remember every form of geometry, where based on the results of the test, the selection mode on the tool was 100% successful, the process in the learning mode and the question mode had a success rate of more than 80%.